Trichoteiromania in adults - Anastasia N. Mareeva; Irina M. Pichugina (Vestnik Dermatologii i Venerologii, 2020)
This paper describes two clinical cases of a rare auto-destructive hair pathology trichoteiromania. In the literature a few cases of trichoteiromania are described, it leads to non-cicatricial hair loss as a result of their rubbing and is characterized by splitting and damaging of the hair shaft.